2016
DOI: 10.1016/j.drugalcdep.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with substance use disorder and assent/consent: Empirical data on understanding biobank risks in genomic research

Abstract: Objective This study assessed whether a customized disclosure form increases understanding for adolescents with substance use disoder (SUD) when compared to a standard disclosure for genomic addiction research. Method We gathered empirical data from adolescents with SUD, family members, former patients followed since adolescence, and community counterparts. The study was conducted in four stages. Stage 1: national experts (n=32) identified current, future, speculative risks of broadly shared biobanks. Stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…However, the one study describing the standard form to be more effective was the only one where the intervention and the standard form did not cover the same content, but were used for two different clinical trials [9]. A non-randomized study found the enhanced form to significantly improve understanding in adolescent patients suffering substance use disorder but to have no effect in the control group of healthy adolescents [14]. Another randomized study tested block text format against questions and answers (Q&A) as well as story format, but failed to provide statistical calculations for the means of correct answers.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, the one study describing the standard form to be more effective was the only one where the intervention and the standard form did not cover the same content, but were used for two different clinical trials [9]. A non-randomized study found the enhanced form to significantly improve understanding in adolescent patients suffering substance use disorder but to have no effect in the control group of healthy adolescents [14]. Another randomized study tested block text format against questions and answers (Q&A) as well as story format, but failed to provide statistical calculations for the means of correct answers.…”
Section: Study Characteristicsmentioning
confidence: 99%